Циклізація поезії Катерини Каленіченко - Біляцька, В. П.; Полякова, С. В. (My University, 2024)
У статті йдеться про лірику збірок «Переливи радості й печалі», «Під небесами осяйними», «Впивайся музикою, ліро» Катерини Каленіченко. Кожну збірку поезій поділено на авторські цикли з провідним ліричним образом, який є часткою його структури, наголошується на способах компонування поетичних текстів у цикли як специфічному виді контексту.

The article deals with the lyrical collections of Kateryna Kalenichenko, including "Ripples of Joy and Sorrow", "Under Radiant Skies", and "Savor the Music, Lyre". Each poetry collection is divided into authorial cycles centered around a primary lyrical image, which forms an essential part of the structure. The article emphasizes the techniques of organizing poetic texts into cycles as a unique contextual approach.
Cyclіс structure in Kateryna Kalenichenko’s poetry
Keywords: ліричний цикл; поезія; циклізація; композиційний прийом; Катерина Каленіченко; yrical cycle; poetry; cyclic structure; compositional technique; Kateryna Kalenichenko